2015
DOI: 10.1111/add.12849
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of internet gaming disorder in German adolescents: diagnostic contribution of the nine DSM‐5 criteria in a state‐wide representative sample

Abstract: Based on a state-wide representative school survey in Germany, endorsement of five or more criteria of DSM-5 internet gaming disorder (IGD) occurred in 1.16% of the students, and these students evidence greater impairment compared with non-IGD students. Symptoms related to 'give up other activities', 'tolerance' and 'withdrawal' are most relevant for IGD diagnosis in this age group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

46
346
18
22

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 476 publications
(475 citation statements)
references
References 31 publications
46
346
18
22
Order By: Relevance
“…These findings contrast with those of two recent studies (i.e., Lemmens et al, 2015;Rehbein et al, 2015) that found "escape" was the most frequently endorsed criteria, while "negative consequences" (termed as "conflict" in Lemmens et al's study, and "risk/lose relationship/opportunities" in Rehbein et al's study) was the least endorsed in both the whole sample and among those meeting five or more IGD criteria.…”
Section: Discussioncontrasting
confidence: 93%
See 3 more Smart Citations
“…These findings contrast with those of two recent studies (i.e., Lemmens et al, 2015;Rehbein et al, 2015) that found "escape" was the most frequently endorsed criteria, while "negative consequences" (termed as "conflict" in Lemmens et al's study, and "risk/lose relationship/opportunities" in Rehbein et al's study) was the least endorsed in both the whole sample and among those meeting five or more IGD criteria.…”
Section: Discussioncontrasting
confidence: 93%
“…Based on conditional inference tree analysis, Rehbein et al (2015) reported that the criterion "giving up other activities" and "tolerance" were key in identifying IGD. Being associated with more severe IGD levels in the present study may help explain why endorsement of these criteria corresponds to a high probability of a positive IGD diagnosis (Rehbein et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, based on the differences in their motives and the consequences of their activity, he argued that one of them appeared to be addicted while the other was merely engaged. These findings were supported further by the small-tomoderate correlations between gaming time and addiction reported in several studies [14][15][16][17].…”
supporting
confidence: 77%